Influence of core halogenation on the electronic structure of naphthothiadiazole derivatives [data] - Ajdari, Mohsen; Landwehr, Felix; Hoffmann, Marvin; Hoffmann, Hendrik; Bunz, Uwe H. F.; Dreuw, Andreas; Tegeder, Petra (Universität, 2024)
Underlying data for figures in the paper "Influence of Core Halogenation on the Electronic Structure of Naphthothiadiazole Derivatives"
Gefördert durch: Deutsche Forschungsgemeinschaft: SFB 1249: N-heteropolycycles as functional materials: 281029004-SFB 1249, Projects A05, B01, and B06
Gesehen am 24.06.2024
Keywords: Forschungsdaten; Datenbank